Estimation of Serum Aldosterone and Electrolytes in Pregnancy Induced Hypertension (Tikrit Journal of Pharmaceutical Sciences, 2023)
Pregnancy Induced Hypertension(PIH) is one of the most frequent complications of pregnancy , however little is known about its etiology. The renin angiotensin aldosterone system(RAAS) has been implicated in the pathogenesis of PIH. The study of serum electrolytes is gaining ground in the pathophysiology of hypertension. The study sample consist of 50 normal non pregnant women, 50 normotensive pregnant women, and 50 preeclamptic pregnant women in their third trimester in Mosul city. The aim of this study was designed to evaluate the role of serum aldosterone and the serum electrolytes in pathogenesis of PIH. The results of this study showed that there was a highly significant reduction (P